1993
DOI: 10.1007/bf01338831
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic patterns of volatiles identified in Dufour's gland extracts from queens and workers of the primitively eusocial halictine bee,Lasioglossum malachmum (Hymenoptera: Halictidae)

Abstract: SummaryOntogenetic patterns of volatile compounds identified in Dufour's gland extracts from queens and workers of the primitively eusocial sweat bee Lasioglossum malachurum (K.) were compared. Only young unmated queens showed high proportions of isopentenyl esters, while macrocyclic lactones were dominant in old breeding queens, spring queens, and workers. In young queens the relative and absolute amounts of volatiles changed one day after mating. A discriminant analysis revealed significant differences in od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Branch lengths do not have any significance. References: 1 Rosi et al (2001), 2 Mehrnejad and Copland (2007), 3 Vardal (2006), 4 Guillot et al (1974), 5 Vinson and Guillot (1972), 6 Lawrence and Akin (1990), 7 Vinson (1978), 8 de Freitas et al (2004, 9 Marris et al (1996), 10 Huang et al (2008), 11 Cane (1981), 12 Duffield et al (1983), 13 Hefetz (1987), 14 Ayasse et al (1990b), 15 Hefetz et al (1979), 16 Albans et al (1980), 17 Cane (1981), 18 Guedot et al (2006), 19 Cane (1981), 20 Brooks and Cane (1984), 21 Ayasse et al (1990a), 22 Smith et al (1985), 23 Barrows (1975a), 24 Barrows et al (1975b), 25 Ayasse et al (1993), 26 , 27 Hefetz (1987), 28 Smith and Wenzel (1988), 29 Cane and Carlson (1984), 30 Duffield et al (1984), 31 Norden et al (1980), 32 Hefetz et al (1982), 33 Shimron et al (1985), 34 Frankie and Vinson (1977), 35 Vinson et al (1978), 36 Katzav-Gozansky et al (2002), 37 Sole et al (2002), 38 Oldroyd et al (2002), 39 Katzav-Gozansky et al (2007), 40 Malka et al (2008), 41 Tengö et al (1991), 42 …”
Section: Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Branch lengths do not have any significance. References: 1 Rosi et al (2001), 2 Mehrnejad and Copland (2007), 3 Vardal (2006), 4 Guillot et al (1974), 5 Vinson and Guillot (1972), 6 Lawrence and Akin (1990), 7 Vinson (1978), 8 de Freitas et al (2004, 9 Marris et al (1996), 10 Huang et al (2008), 11 Cane (1981), 12 Duffield et al (1983), 13 Hefetz (1987), 14 Ayasse et al (1990b), 15 Hefetz et al (1979), 16 Albans et al (1980), 17 Cane (1981), 18 Guedot et al (2006), 19 Cane (1981), 20 Brooks and Cane (1984), 21 Ayasse et al (1990a), 22 Smith et al (1985), 23 Barrows (1975a), 24 Barrows et al (1975b), 25 Ayasse et al (1993), 26 , 27 Hefetz (1987), 28 Smith and Wenzel (1988), 29 Cane and Carlson (1984), 30 Duffield et al (1984), 31 Norden et al (1980), 32 Hefetz et al (1982), 33 Shimron et al (1985), 34 Frankie and Vinson (1977), 35 Vinson et al (1978), 36 Katzav-Gozansky et al (2002), 37 Sole et al (2002), 38 Oldroyd et al (2002), 39 Katzav-Gozansky et al (2007), 40 Malka et al (2008), 41 Tengö et al (1991), 42 …”
Section: Functionmentioning
confidence: 99%
“…Such compounds have also been implicated in marking the nest entrance, helping in locating the nest within the nesting site (Hefetz 1987). In the sweat bee Lasioglossum malachurum (Halictidae), the pattern of Dufour's gland compounds was found to differ between virgin and mated queens, suggesting a possible involvement in mating and courtship (Ayasse et al 1993). Mated queens had higher proportion of macrocyclic lactones (used in nest construction), and lower proportion of isopentyl esters (volatiles), as compared to virgin queens, and the composition of Dufour's gland compounds was found to change within one day of mating (Ayasse et al 1993).…”
Section: B) Aculeatamentioning
confidence: 99%
See 1 more Smart Citation
“…In field bioassays, dummies impregnated with these "artificial head" blends were exposed to drone aggregations. The drones' reaction clearly indicated that they could recognize the scent of a young queen (Ayasse et al, 1990(Ayasse et al, , 1993. ), but also a distinct age-related pattern that gradually changes, in particular during the first 2 wk after emergence.…”
Section: Introductionmentioning
confidence: 89%
“…Is there a post-copulation message indicating to the drones that this young queen is no longer receptive? In the primitively eusocial halictine bee Lasioglossum malachurum, the volatile composition of the Dufour's gland secretion changes significantly within 1 d after mating (Ayasse et al, 1993). It is interesting to note that the butyrates found in high proportions only in such S postica queens show some structural relationship to certain acetates which are typical sex pheromones in Lepidopteran females (Arn et al, 1992).…”
Section: Incipientmentioning
confidence: 99%